Clinical sociology and anti-oppressive approach: deepen reflections on the social work research posture in a context of interculturality in Canada. (Clinical Sociology Review, 2022)
Intercultural relationships in the context of social work are themes integrated into social work learning. Approached in research or intervention, interculturality requires questioning one's posture and the framework of the encounter with others. This article aims to show how the socio-clinical approach and anti-oppressive practice make it possible to create a benevolent space of inquiry for research in an intercultural context, specifically dealing with issues of racism. The aim here is not to show the analysis of research data, but to use it to show in what space the stories of the research participants were heard.